URoom: UTP Room Booking & Management System - Nurzaidi, Amin Nur Idzuan (IRC, 2019)
This paper describes the concepts and method for UTP Room Booking and Management System mobile application development. This system will be created on a mobile application platform based on the UTP Room Registration System. This project's primary goal is to provide the student with a distinct room reservation system that differs from the present system of registration. The centred project is to provide students with a more effective and user-friendly system to use. The problem with the present condition is the double booking of registered rooms and the system crash leads to a more complex and tedious operation for both the student parties and the management sides to resolve the issue. For the project, the scope focuses on one of the room registration system's functions which is requesting for temporary room reservation and event room reservation. UTP Room Booking and Management System will therefore be a foothold for improving the present system used in the UTP by beginning with replacing the traditional temporary room booking request method. Agile SDLC model is implemented for the project innovations and will be explained in one of this paper's sections. In this article there will be five chapters: introduction, literature review, methodology, result and discussion, and finally, conclusion and recommendation of the UTP Room Booking and Management System.